Sistem Pemberian Kredit di Koperasi Simpan Pinjam (KSP) Sejahtera Abadi Maumere - Katharina Da Silva; H. Amir Djonu; Muhammad Syahrun (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The Credit Granting System at the Sejahtera Abadi Maumere Saving and Loans Cooperative (KSP). Paper. Maumere. Faculty of Social Sciences Education & Humanities. IKIP Muhammadiyah Maumere, 2023.This study aims to determine the systems and procedures for extending credit at the Sejahtera Abadi Maumere Saving and Loans Cooperative (KSP). The type of research used is qualitative research with data sources in the form of primary data and secondary data obtained from KSP Sejahtera Abadi Maumere and costumers. Data collection using the method of observation, interviews and documentation. While the analysis technique is carried out on data from preliminary studies or secondary data that will be used to determine the research focus. Procedures for extending credit at KSP Sejahtera Abadi Maumere include: submitting credit applications, preparing documents, analyzing credit applications, processing credit disbursements, filing and storing documents, paying installments, paying off and returning guarantees.